Current-induced picosecond magnetization dynamics in a Ta/CoFeB/MgO hall bar. (2nd July 2019) - Spicer, T M; Durrant, C J; Keatley, P S; Kruglyak, V V; Chen, W; Xiao, G; Hicken, R J
Abstract: Time-resolved Kerr microscopy (TRSKM) has been used to explore the small amplitude picosecond magnetization dynamics induced by spin–orbit torques in a Ta(4 nm)/Co40 Fe40 B20 (1 nm)/MgO(1.6 nm)/Ta(1 nm) Hall bar structure. The time dependent polar magneto optical Kerr effect was recorded following injection of a current pulse of 70 ps duration. Macrospin simulations provide a reasonable description of the precession and a transient background response as the field strength and current polarity are varied, while confirming that the in-plane spin–orbit torque is dominant within this system. Increasing the current density within the simulations leads to coherent magnetization reversal. Inclusion of a modest in-plane bias field is found to reduce both the switching current and the time required for switching. The orientation of the in-plane field relative to the direction of the current determines whether the magnetization can be switched backwards and forwards by current pulses of the same or opposite polarity.